Genome‐based survey of the SARS‐CoV‐2 BF.7 variant from Asia. Issue 4 (6th April 2023) - Scarpa, Fabio; Giovanetti, Marta; Azzena, Ilenia; Locci, Chiara; Casu, Marco; Fiori, Pier Luigi; Ciccozzi, Alessandra; Imperia, Elena; Bazzani, Liliana; Borsetti, Alessandra; Maruotti, Antonello; Pascarella, Stefano; et al.
Abstract: The SARS‐CoV‐2 BF.7 variant represents one of the most recent subvariant under monitoring. At the beginning of the 2023 it caused several concerns especially in Asia because of a resurge in COVID‐19 cases. Here we perform a genome‐based integrative approach on SARS‐CoV‐2 BF.7 to shed light on this emerging lineage and produce some consideration on its real dangerousness. Both genetic and structural data suggest that this new variant currently does not show evidence of an high expansion capability. It is very common in Asia, but it appears less virulent than other Omicron variants as proved by its relatively low evolutionary rate (5.62 × 10 −4 subs/sites/years). The last plateau has been reached around December 14, 2022 and then the genetic variability, and thus the viral population size, no longer increased. As already seen for several previous variants, the features that may be theoretically related to advantages are due to genetic drift that allows to the virus a constant adaptability to the host, but is not strictly connected to a fitness advantage. These results have further pointed that the genome‐based monitoring must continue uninterruptedly to be prepared and well documented on the real situation.